Adenomyoepithelioma of the breast: a proposal for classification. Issue 4 (13th June 2021) - Rakha, Emad; Tan, Puay Hoon; Ellis, Ian; Quinn, Cecily
Abstract : Breast lesions with a prominent myoepithelial cell component constitute a heterogeneous group of benign and malignant neoplastic proliferations. These lesions are often dual epithelial–myoepithelial, but may be purely myoepithelial cell in nature. Benign epithelial–myoepithelial lesions typically maintain the morphology and immunophenotype of the normal bilayer epithelial myoepithelial structures. However, the distinction between the two cell components is not always clear‐cut in malignant lesions in which the histogenesis of myoepithelial cells remains uncertain. Neoplastic biphasic epithelial–myoepithelial lesions of the breast include adenomyoepithelioma (AME), pleomorphic adenoma and adenoid cystic carcinoma. Four histological patterns of classical AME have been described: tubular, lobulated, spindle‐cell and adenosis variants. Overlapping patterns occur and some AMEs display an intraductal papillary pattern that may represent a fifth variant. AME can be benign or malignant. Classical AME may show atypical features, which are not sufficient for the diagnosis of malignancy (atypical AME). Atypical AME is recognised as a lesion of uncertain malignant potential with limited metastatic capability. Based on the histological features, we propose a classification of malignant AME (M‐AME) into three variants: M‐AME in situ, M‐AME invasive and AME with invasive carcinoma. In this review, we provide an overview of myoepithelial lesions of the breast focusing on the classification of AME to improve not only the consistency of reporting but also help to guide further management decision‐making. Abstract :